Treatment of female crack users: An analysis from the literature (Research, Society and Development, 2021)
Aims: Identify and analyze the published articles of female crack users treatment. Method: Integrative review of the literature, based on scientific productions available at the bases: BVSpsi, Pepsic, Socindex and Pubmed. Thirty-six qualitative and field studies were selected, which included women users of crack as study subjects. Results: Stigma was the main barrier to treatment. Authors reviewed suggest that a gender perspective should be adopted in the treatment of women who use crack, and the inclusion of the family can ease conflicts and favor care actions. Finally, authors mention that the use of safe rooms may be a protection factor against the various situations of violence present in the territory. Conclusion: It is essential to include women’s issues I the definition of treatment for women crack users. This article may indicate gaps in field surveys that need to be deepened and broadened to other realities.